PENGUKURAN FREKUENSI BUNYI BONANG BARUNG LARAS PELOG GAMELAN JAWA MENGGUNAKAN PERANGKAT LUNAK VISUAL ANALYSER - , NANDANG RAHAYU N ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research aims to investigate the frequency characteristics of sound of gamelan, especially Bonang Barung Laras Pelog. Bonang Barung Laras Pelog is one of gamelanâs set which does not have standard tone frequency like modern musical instruments. Gamelan tuning is carried out by experts with traditional way, approximately based on their experience and rely on their hearing and feeling. That method produce each gamelan which does not have standard tone frequency. The result of this research is expected can be reference for gamelan tone frequency standardization, especially for Bonang Barung Laras Pelog. Research is executed in three (3) samples of different Bonang Barung Laras Pelog. Resonance frequency of each wilahan measured by beat it with constant relative pressure (Concurrently, sound recorded by microphone that related with computer that equiped with Visual Analyser software). Visual Analyser software will display frequency and spectrum of the sound that produced. Data that gathered to analyzed and got resonance frequency value of each wilahan in three (3) samples of Bonang Barung Laras Pelog. The result shows irregularity between them. Resonance frequency value in three (3) samples taken the average value (f0) and its error value (Îf0) for each low tone wilahan from wilahan 1 through 7 are (302Â± 8) Hz, (322Â±8) Hz, (351Â±8) Hz, (407Â±8) Hz, (433Â±9) Hz, (459Â±9) Hz, dan (508Â±9) Hz and for each high tone wilahan from wilahan 1â through 7â are (583Â±10) Hz, (635Â±10) Hz, (688Â±11) Hz, (815Â±12) Hz, (867Â±12) Hz, (923Â±13) Hz, dan (1014Â±14) Hz.